Climate and soil factors drive the functional and phylogenetic assembly of Qinghai-Tibetan grassland communities via multiple paths - Xiaomei Kang; Yanjun Liu; Xinyang Wu; Lijie Duan; Jiachang Jiang; Aoran Zhang; Wei Qi (Basic and Applied Ecology)
Elucidating the functional and phylogenetic community structures is essential for understanding coexistence of plant species and biodiversity within ecosystems. Despite their significance, the manner in which these structures change along environmental gradients has not been explored extensively. We estimated the phylogenetic diversity (PD) and community-weighted mean (CWM) and functional diversity (FD) values of four key functional traits in 558 grassland plots across the Qinghai-Tibetan Plateau (QTP) and assessed their relationship to climate and soil factors. Our results demonstrate that climate has a more pronounced direct impact on community structures than soil properties. Moreover, the indirect effect of climate through soil conditions does not significantly contribute to the observed patterns in functional and phylogenetic diversity. Annual and seasonal temperature was a reliable predictor of functional structure of plant or organ size traits, especially CWM of leaf size and CWM and FD of plant height. CWM and FD of most leaf traits and PD were correlated positively with multiple precipitation factors and humidity but negatively with sunshine hours. We highlight the importance of temperature, local resource availability and environmental filtering in governing the functional and phylogenetic structures of the QTP grassland communities. These findings have the potential to improve our predictions of climate change impacts on plant community assembly.